European Society of Anaesthesiology evidence-based and consensus-based guideline on postoperative delirium. Issue 4 (April 2017) - Aldecoa, César; Bettelli, Gabriella; Bilotta, Federico; Sanders, Robert D.; Audisio, Riccardo; Borozdina, Anastasia; Cherubini, Antonio; Jones, Christina; Kehlet, Henrik; MacLullich, Alasdair; Radtke, Finn; Riese, Florian; et al.
Abstract : The purpose of this guideline is to present evidence-based and consensus-based recommendations for the prevention and treatment of postoperative delirium. The cornerstones of the guideline are the preoperative identification and handling of patients at risk, adequate intraoperative care, postoperative detection of delirium and management of delirious patients. The scope of this guideline is not to cover ICU delirium. Considering that many medical disciplines are involved in the treatment of surgical patients, a team-based approach should be implemented into daily practice. This guideline is aimed to promote knowledge and education in the preoperative, intraoperative and postoperative setting not only among anaesthesiologists but also among all other healthcare professionals involved in the care of surgical patients.